2009
DOI: 10.1117/12.808547
|View full text |Cite
|
Sign up to set email alerts
|

Cell viability studies of PEG-thiol treated gold nanorods as optoacoustic contrast agents

Abstract: Rod shaped gold nanoparticles are synthesized using cetyltriammonium bromide (CTAB) as a major component of growth solutions. This surfactant is toxic to cells, but is at the moment unavoidable when monodisperse and high yield nanorods are to be synthesized. CTAB is found coating side walls of the nanoparticles and plays a role in maintaining colloidal stability. It may be displaced using thiolated PEG which is non-toxic to cells. Here we report on systematic studies of cell viability of such PEGylated nanorod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
11
1
Order By: Relevance
“…6 Previous studies of various types of nanoparticles have indicated that their surface chemistry strongly influences cell toxicity and uptake. [8][9][10][11][12][13][14][15] GNR synthesis requires the surfactant cetyltrimethylammonium bromide (CTAB), 16 and GNR-CTAB not only have poor stability in biological solutions, but also exhibit significant cytotoxicity. 13,15,17,18 Several surface coatings have been proposed in order to reduce the apparent toxic effect of the GNRs, such as by "cloaking" the CTAB-GNRs with polyelectrolytes, 13 phospholipids, 5 or exchanging the CTAB with another molecule such as thiolated PEG.…”
mentioning
confidence: 99%
“…6 Previous studies of various types of nanoparticles have indicated that their surface chemistry strongly influences cell toxicity and uptake. [8][9][10][11][12][13][14][15] GNR synthesis requires the surfactant cetyltrimethylammonium bromide (CTAB), 16 and GNR-CTAB not only have poor stability in biological solutions, but also exhibit significant cytotoxicity. 13,15,17,18 Several surface coatings have been proposed in order to reduce the apparent toxic effect of the GNRs, such as by "cloaking" the CTAB-GNRs with polyelectrolytes, 13 phospholipids, 5 or exchanging the CTAB with another molecule such as thiolated PEG.…”
mentioning
confidence: 99%
“…Methods may include increasing the nanoparticle size to take advantage of the Enhanced Permeability and Retention (EPR) effect of tumors and limiting free diffusion into healthy tissues. Also, PEGylation of the nanoconjugate may prevent recognition by the reticuloendothelial system and increase circulation time [ 21 ]. Third, methods of delivering the intense pulsed light to the tumors must be established.…”
Section: Future Workmentioning
confidence: 99%
“…For the in vivo stage of our proposed work we may use different shaped and sized AuNPs including the advanced Au nanorods [21] and Au nanoshells [22]. AuNPs heat up as a result of absorption of visible light, which makes them suitable for use in cancer photothermal treatment.…”
Section: Background and Introductionmentioning
confidence: 99%
See 2 more Smart Citations